0024 ARC Genotype Modulates EEG Spectral Power Following Total Sleep Deprivation. (25th May 2022) - Satterfield, Brieann; Finlay, Myles; Skeiky, Lillian; Lawrence-Sidebottom, Darian; Schmidt, Michelle; Wisor, Jonathan; Van Dongen, Hans
Abstract: Introduction: Sleep homeostasis is manifested by a robust increase in slow wave sleep (SWS) following acute total sleep deprivation (TSD), with concomitant changes in spectral power of the non-REM (NREM) sleep EEG marked by substantial interindividual differences. We previously found that a single nucleotide polymorphism of the activity-regulated cytoskeleton associated protein (ARC) gene modulates SWS rebound following TSD. Here we sought to determine whether ARC genotype is also associated with interindividual differences in spectral power of the NREM sleep EEG. Methods: 50 healthy adults (27.3±4.9 years; 28 females) participated in one of two in-laboratory studies. Each participant had a 10h baseline sleep opportunity (22:00–08:00), 38h TSD, and a 10h recovery sleep opportunity (22:00–08:00). Sleep periods were recorded polysomnographically and visually scored according to AASM criteria. Genomic DNA was assayed for the ARC c.*742 + 58C>T non-coding SNP, rs35900184. Log-transformed NREM sleep EEG spectral power (C3-M3 derivation) over 0.2 Hz frequency bins in each of four frequency bands – delta (0.8–4.0 Hz), theta (4.2–8.0 Hz), alpha (8.2–12.0 Hz), and beta (12.2–16.0 Hz) – was analyzed by band using mixed-effects ANOVA with fixed effects for ARC genotype, night (baseline, recovery), frequency bin, and their interactions. Analyses included study and age as covariates and a random effect over subjects on the intercept. Results: The genotype distribution in this sample was 33 C/C homozygotes, 11 C/T heterozygotes, and 6 T/T homozygotes. There was a significant ARC by night interaction in the theta (F2, 1833=5.94, p=0.003) and alpha (F2, 1833=8.58, p<0.001) bands. Compared to baseline sleep, during recovery sleep C/C homozygotes had 18.9% more theta power and 8.7% more alpha power, C/T heterozygotes had 17.9% more theta power and 7.6% more alpha power, and T/T homozygotes had 20.0% more theta power and 15.1% more alpha power. Conclusion: Our results show that ARC genotype mediates the NREM sleep EEG response to TSD; compared to C allele carriers, homozygosity for the T allele is associated with a much more pronounced increase in alpha power, as well as a larger increase in theta power. The functional implications of this ARC effect remain to be determined. Support (If Any): ONR N00014-13-1-0302, NIH R21CA167691, and USAMRDC W81XWH-18-1-0100.